Analisis Penyebaran Penyakit Filariasis Menggunakan Model SEIR Di Provinsi Sumatera Utara - Muhammad Mukhlis; Fazrina Saumi; Ulya Nabilla (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
North Sumatra is one of the endemic areas of tropical diseases, one of which is filariasis. Filariasis or elephantiasis is a disease transmitted through mosquitoes and can cause permanent physical disability for sufferers. In 2015, there were 127 filariasis sufferers. This number has increased to 164 patients in 2017. As a prevention effort, the government provides mass treatment for people living in endemic areas of the disease. Therefore, this study aims to determine the model of spread and the effect of treatment on these communities. This study uses an SEIR model consisting of susceptible humans (S_h), infected humans (E_h), infected humans (I_h), and immune humans (R_h). The data used is data on filariasis sufferers in North Sumatra in 2010-2019, obtained from the North Sumatra Health Office. The data were analyzed based on the equilibrium point, stability, basic reproductive ratio, and numerical simulation. The results showed that based on the SEIR model, filariasis treatment could suppress transmission in endemic areas.